Road Safety Concerns Related to the Overtaking Side Distance of Cyclists: – Examples of the Széchenyi Chain Bridge and Határ út in Budapest - Felföldi, Péter (Magyar Rendészet, 2025)
In Hungary, the issue of maintaining the overtaking lateral distance has been persistent among cyclists and law enforcement officers over the last 5 years. Opinions are also divided among road users as to the dangers of keeping or not keeping the lateral distance and, if the danger is real, what can be done to improve road safety. However, this issue can also be approached from the perspective of what factors might influence the ability of faster, motorised drivers to maintain this (perceived) safe lateral distance. In addition, it is legitimate to ask whether the degree of danger posed by different categories of vehicles and by different routes supports the importance of maintaining a lateral distance at different locations. In this study, I conducted an empirical data collection in downtown environment with scientific accuracy to gain insight into drivers’ side distance keeping attitudes on Széchenyi Chain Bridge and Határ út in Budapest. As a result of the measurements, it has been shown that overtaking on the Chain Bridge at similar lane widths with a continuous line also occurs, while maintaining a smaller overtaking lateral distance. This result could be used as input for a possible traffic engineering revision in the future.